2019
DOI: 10.3390/cancers11111813
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Accuracy of Liquid-Based Oral Brush Cytology in Screening for Oral Squamous Cell Carcinoma

Abstract: This study evaluates the accuracy of the results of liquid-based oral brush cytology and compares it to the histology and/or the clinical follow-ups of the respective patients. A total of 1352 exfoliated specimens were collected with an Orcellex brush from an identical number of oral lesions, then cytological diagnoses were made using liquid-based cytology. The final diagnoses in the study were 105 histologically proven squamous cell carcinomas (SCCs), 744 potentially malignant lesions and 503 cases of traumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Our data demonstrate that cells in the gingival sulcus may be a new entry point for the SARS-CoV-2 virus via a high expression of ACE2. In the present research, we first evaluated the expression of ACE2 in various sites of the oral cavity with noninvasive, convenient liquid-based cytology [9]. A recent study suggested that structural variations in human ACE2 may influence its binding with the SARS-CoV-2 spike protein [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data demonstrate that cells in the gingival sulcus may be a new entry point for the SARS-CoV-2 virus via a high expression of ACE2. In the present research, we first evaluated the expression of ACE2 in various sites of the oral cavity with noninvasive, convenient liquid-based cytology [9]. A recent study suggested that structural variations in human ACE2 may influence its binding with the SARS-CoV-2 spike protein [20].…”
Section: Discussionmentioning
confidence: 99%
“…Background characteristics included age, sex, smoking and alcohol consumption. The preparation procedure for liquid-based cytology differs from that of the conventional preparation of brush cytology [9]. In the conventional preparation, multiple exfoliated cells are spread out on multiple glass slides immediately after the collection of the cells.…”
Section: Methodsmentioning
confidence: 99%
“…The use of cytobrush for further liquid-based cytology is a well-tolerated and minimally invasive technique for collecting samples [16,21]; however, a systematic review by Alsarraf et al indicates variable results without clear recommendations on the effectiveness of this technique for the diagnosis of lesions on the head and neck [22]. In this regard, our cytology results from samples performed before treatment, when compared with the biopsy (gold standard), showed a high sensitivity (over 80%) and specificity (100%).…”
Section: Discussionmentioning
confidence: 99%
“…Liquid-based cytology (LBC) is a non-invasive technique that can be used to diagnose OED and OSCC. However, the false negative rate (FNR) has been reported to be 15.1-31.3% [7][8][9][10]; in particular, Kondo et al [10] showed that 81% cases of mild or moderate dysplasia were cytologically diagnosed as negative for any intraepithelial lesion or malignancy (NILM). False negative results can lead to undiagnosed carcinoma progression and mortality, if no further treatments are undertaken.…”
Section: Introductionmentioning
confidence: 99%